Deslocados internos e direito à moradia no contexto dos megaeventos esportivos no Brasil: Direitos humanos relativizados pela colonialidade do poder - Fernandes, Karina Macedo (Universidade do Vale do Rio dos Sinos, 2014)
The purpose of the present study is to demonstrate that the issue of internal displacements is featured in Brazil as a consequence of forced remotions that go through violations of the human rights of housing and the city, during the process of preparation and execution of sports mega-events, in reason of the developing model addopted by the brazilian State, flagrantly marked by coloniality of power. From that, the research intends to analyze the current displaying of internal displacements around the world, the causes and the main human rights' s violations that occur in this context, as well as the main protection and assistence manifestations adressed to them. Furthermore, it intends to analyze in which measurement the institutions and the modern State features are determined by a colonial matrix of power, therefore allowing a model of progress and development that deepens unequality, conceals identities and silences conflicts. By this notion, we shall verify that this modern/capitalist/colonial model of development adopted by Brazil has got as consequece a pattern of discriminatory, excludent and opressive city modernization process and urban planning, enhanced by the scope of the preparation of major cities of the country for the accomplishment of sports mega-events, specially through compulsory evictions and the violation of the housing right. Besides the verification of traditional causes of forced internal displacements, the need of casting the affected by forced removals such as internally displaced broadens possibilities of legal protection and also collective, subjective and institutional awareness about this matter that, among others, was unveiled by the processes of preparation for the mega-events' execution in Brazil. Based on the theoretical framework of decolonial thought, analyzes the coloniality of power within the category of human rights violations identified in the context of mega-events, from the developmental logic in which these violations are legitimized. Through bibliographic, documental and non-participant observation analysis on who is directly and indirectly involved in the tensions of the process of mega events preparation, specially in the Porto Alegre town, we intend to reveal more precisely the reality faced in this harvest, as well as to identify the theoretical fundamentals which explain them, in order to concretize a strategic knowledge of human rights so it shall not be confined to social speech, but that it deepens in causes and increases arguments to act and generate critical dispositions and antagonists facing the structure or hegemonic social order.
Keywords: Deslocados internos; Desenvolvimento; Colonialidade do poder; Megaeventos; Direito à moradia; Internally displaced; Development; Coloniality of power; Mega-events; Housing rights; ACCNPQ::Ciências Sociais Aplicadas::Direito